Indirect charge transfer of holes via surface states in ZnO nanowires for photoelectrocatalytic applications. Issue 15 (1st August 2022) - Batista-Grau, P.; Fernández-Domene, R.M.; Sánchez-Tovar, R.; Blasco-Tamarit, E.; Solsona, B.; García-Antón, J.
Abstract: In this work, ZnO nanowires with high aspect ratio were obtained by fast and simple electrochemical anodization. Morphological, structural and photoelectrochemical characteristics of the synthesized ZnO nanowires were evaluated by using different techniques: field emission scanning electron microscopy, atomic force microscopy, high resolution transmission electron microscopy, Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, UV–VIS spectroscopy, Mott-Schottky analysis and photoelectrochemical impedance spectroscopy. The synthesized ZnO nanowires presented high roughness and high crystallinity. Besides, surface defects were identified in the sample. The value of the donor density ( N D ) was in the order of 10 19 cm −3 in the dark and 10 20 cm −3 under illumination. In addition, the ZnO nanowires presented good photosensibility, with a photocurrent density response 85 times higher than a ZnO compact layer, and lower resistance to charge transfer. The charge transfer processes taking place at the ZnO/electrolyte interface were studied, since these processes strongly influence the photoelectrocatalytic efficiency of the material. According to the results, the charge transfer of holes in the synthesized ZnO nanowires occurs indirectly via surface states. In this regard, surface states may be an important feature for photoelectrocatalytic applications since they could provide lower onset voltages and higher anodic current densities. Graphical abstract: Image 1 Highlights: ZnO high aspect ratio nanowires were synthesized by simple anodization. ZnO nanowires presented high crystallinity, as showed by XRD and Raman spectroscopy. Raman spectra and XPS showed that the ZnO surface presented structural disorders. ZnO/electrolyte interface was studied by photoelectrochemical impedance spectroscopy. Holes charge transfer in the ZnO nanowires occurs indirectly via surface states.